Proposta de atuação fonoaudiológica para estudantes de comunicação: efeitos de dois tipos de treinamento - Fernandes, Maria Cristina de Menezes Borrego [UNIFESP] (2017)
Objective: To compare the effects of two voice improvement programs on communication students. Methods: The study was carried out in two phases. Phase 1 – it was performed the speech language pathology practice pathway mapping to oral expression. Next, two training programs were developed: Voice and Oral Communication Development Group (VG) and Oral Expression and Communication Development Group (EG). Each group had an average of 20 participants for 8 weeks, two hours training per week. In the last step of phase 1, the Speech-Language Pathologists (SLP) trainers were instructed. On phase 2, the subjects were recruited and randomly divided into the groups. Participated 103 communication students, 46 students in VG (16 men and 30 women, mean age 20.6 years) and 57 students in EG (10 men and 47 women, mean age 20.2 years) that were distributed in 5 groups throughout the year: G1 (N=19), G2 (N=24), G (N=20), G4 (N=25), and G5 (N=15). The following questionnaires were addressed: Communication Involvement and Efficiency Self-Assessment during training, Training Form and Content Assessment, Group Climate Questionnaire – GCQ, Voice self-assessment and Communication Competence Test – TACCOM. The participants had an informative text reading recorded at the beginning and end of training in which was performed voice general grade of deviation perceptual analysis, reading comparison and best emission characterization according to selected parameters. Results: EG participants reported to be more involved to training and evaluated their communication more efficient in comparison to VG. Training form and content had good evaluation and, despite the differences between the trainings, the grades were similar to both groups, with group engagement climate predominance in VG and EG. The students assessed their voice and communication better after training, and there were no differences between the studied groups. Voice general grade of deviation was classified as absent in the groups, pre and post training. The participants’ reading had better evaluation after training. Regarding the reasons to this improvement, ‘voice and speech’ and ‘interpretation’ parameters did not had differences in both groups, and ‘clean voice’ and ‘involvement’ demonstrated striking differences in VG and EG. The voice resources speech rate, pauses, intonation, and emphasizes were used properly during text reading after training in both groups. Conclusion: The research results demonstrated positive training effect on communication students in both studied groups. There was difference between pre and post training to all evaluated measures, and the better evaluated readings were correspondent to post training. In VG and EG comparison, the only difference between the groups was Communication Involvement and Efficiency Self-assessment during training in which EG had higher grades. There was no difference between the groups in the others selected parameters. Voice and expression training carried out together seems to be the most indicated speech-language pathology practice regarding communication oral skills improvement.